Explaining Suicide in Organizations: Durkheim Revisited. (8th September 2016) - Clegg, Stewart; Cunha, Miguel Pina E; Rego, Arménio
Abstract: Drawing on Durkheim's concept of anomie, we address the under‐explored phenomenon of anomic suicide in contemporary organizations and discuss the consequences of solidarity for organizations and society. The relations of social solidarity to issues of identity and insecurity are explored through the cases of France Telecom Orange and Foxconn. Remedial implications for organizing, considered as community building, are discussed. Durkheim wrote not only about anomic but also altruistic suicide. We will also analyze examples of this type of suicide. Some tentative suggestions are made for how to organize to minimize the incidence of suicidal violence in organizations.